Male reproductive system of the arrow crab Stenorhynchus seticornis (Inachoididae) - Antunes, Mariana [UNESP]; Zara, Fernando J. [UNESP]; López Greco, Laura S.; Negreiros-Fransozo, Maria L. [UNESP] (Wiley, 2018)
Our aim was to describe the reproductive system of males and the formation of sperm packages in the seminal receptacle (SR) of recently mated females of the arrow crab Stenorhynchus seticornis. The male reproductive system was analyzed, and was described using light microscopy and histological and histochemical methods. The first pair of gonopods was described by means of scanning electron microscopy. Additionally, the dehiscence of spermatophores was tested using samples obtained from the vas deferens of males and from the seminal receptacle of recently mated females. Testes were tubular type, and each vas deferens consisted of three regions: the anterior vas deferens (AVD), including a proximal portion that was filled with free spermatozoa and a distal portion contained developing spermatophores; the median vas deferens (MVD) that contained completely formed spermatophores; and the posterior vas deferens (PVD), which contained only granular secretions. The accessory gland, which was filled with secretions, was located in the transition region between the MVD and the PVD. The spermatophores from the MVD were of different sizes, and none of them showed dehiscence in seawater, whereas those spermatophores in contact with the seminal receptacle were immediately broken. The ultrastructure of the gonopods revealed the presence of denticles at the distal portion, which contribute to the mechanical rupture of the spermatophore wall during the transfer of sperm. The contents of the PVD and accessory gland of males are transferred together with the spermatophores, and are responsible for the secretions observed among the sperm packets in the SR of the female. We suggest that these secretions formed the layers found in the SR of recently mated females, and may play a role in sperm competition in arrow crabs.
Keywords: accessory gland; dehiscence; Majoidea; testis; vas deferens